Захист персональних даних в Європі та в Україні - Могильов, Денис Олексійович (Гуманітарні аспекти цифрового суспільства : тези доп. учасників міжн. наук.-практ. конф. (Харків, 8 груд. 2022 р.), 2022)
The paper analyzes the General Data Protection Regulation. It also studies the legislation of Ukraine in the field of personal data protection. A comparative analysis of the legislation of the EU and Ukraine is carried out in order to harmonize the laws of Ukraine with the EU law in the field of personal data protection.